The prevalence and phenomenological effects of superstitious behaviour in pre-competition sport rituals amongst Asian inter-varsity athletes - Tan, Lloyd Guan Yu (Nanyang Technological University, 2020)
The purpose of the study is to investigate the prevalence and effects of superstitious behaviour in pre-competition sport rituals amongst Asian inter-varsity athletes. Specifically aims to answer two main research questions: 1) If and what kinds of superstitious behaviour do Asian inter-varsity athletes engage in as part of their pre-competition sport rituals and 2) Why do these athletes practice such superstitious behaviour? The study employed a phenological qualitative approach. 15 Asian inter-varsity athletes who engaged with superstitious rituals, or routines with superstitious behaviour, were interviewed for about 45 minutes. Additionally, the participants were required to have gone through minimally a year’s worth of formalised training under the supervision of a coach and participated in an inter-varsity competition as part of the criteria. The interviews were recorded, transcribed into verbatim and analysed along with basic descriptive data. Overarching themes and subthemes from the transcripts were able to identify and recorded items related to the participant’s superstition inclination, sporting experience, nature of superstitions, state anxiety before competitions, locus of control, nature of sports and other reasons for engaging in superstitious sport rituals. The study was able to identify the prevalence of superstition pre-competition sport rituals amongst Asian inter-varsity athletes and presents coaches with the individual zone of optimal functioning as a plausible model in attempting to understand why athletes engage in superstitious sport rituals prior to a competition and the importance of managing their athletes’ arousal levels.